INFLUENCE OF VARIOUS AGROTECHNOLOGICAL MEASURES ON WINTER WHEAT BIOMASS ACCUMULATION IN TYPICAL GRAY SOIL CONDITIONS (British Journal of Global Ecology and Sustainable Development, 2025)
The influence of wheat monoculture without the use of mineral fertilizers, the application of 10 t/ha of organic fertilizers with the rise of pure fallow followed by winter wheat throughout the year, sowing its legumes and perennial alfalfa on the dynamics of wheat biomass accumulation was studied.